Influence of extrafloral nectary phenology on ant-plant mutualistic networks in a neotropical savanna - LANGE, DENISE; DÁTTILO, WESLEY; DEL-CLARO, KLEBER (Ecological entomology, 2013)
Temporal variation has been one remarkable feature of ecological interactions. In ant–plant mutualism, this variation is widely known, although little is understood about the mechanisms that shape these variations. This study tested whether or not the phenology of extrafloral nectaries (EFNs) influences the temporal variation of two properties of an ant–plant interaction network. The network under investigation exhibited a nested pattern and low specialisation over most months. Monthly nestedness and specialisation in the network were negatively correlated, both being influenced by temporal variations in extrafloral nectar production of the plant community. The months of highest activity in the nectaries (August–November) were those when the level of generalisation in the network was at its highest. Although there were temporal variations in the properties of the network, the generalist core of the species remained the same over time. The stable core enhances the coevolutionary importance of ant–plant interactions for the community. Thus, it can be concluded that the phenology of EFNs is one effective mechanism shaping the temporal variation in ant–plant interaction.